Comparative market supply of protein from livestock and fish in the selected urban areas of Rajshahi district in Bangladesh (Research in Agriculture Livestock and Fisheries, 2017)
The study was conducted with the objectives to determine the market availability of animal sourced foods (ASF) and fish, and their share in the supply of biomass and protein through visiting the wet markets of metropolitan and municipality areas of Rajshahi district, Bangladesh. A preset questionnaire was used for recording the biomass weight of different ASF and fish in every four days interval in March, 2016. It was found that the supply of ASF (beef, chevon, chicken and egg) and fish in the metropolitan markets (80.20 and 35.89 t/d, respectively) was significantly higher (P